Interview with Declan Hughes - Mutran, Munira H; Luly, Camila (ABEI Journal, 2014)
In this interview which took place in Rio de Janeiro during the IX Symposium of Irish Studies in South America in 2014, Munira H. Mutran(MHM) and Camila Luly (CL) asked Declan Hughes (DH) questions about hisplays and his crime novels.Keywords: Declan Hughes; fiction; drama.